Identifikasi Struktur Geologi dan Petrografi di sekitar Observatorium Astronomi Lampung Gunung Betung - Hendra Saputra; Luhut P. Siringorongo; Cahli Suhendi; Lea Kristi Agustina (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2020)
Lampung Astronomical Observatory (LAO) is located on Betung Mountain which is quite close to the Semangko active fault zone. Betung Mountain is part of the Bukit Barisan which is located west of the city of Bandar Lampung. This mountain has an altitude of about 1200 meters above sea level. There are 6 interesting stations. Most of the stations are located on the upper slopes of Betung Mountain. In the Talang Aji area, there are 2 springs. The other 4 stations consist of waterfalls with varying heights: Talang Teluk waterfall (30 m), Talang Rabun waterfall (20 m), Betung waterfall consists of two minor terraced waterfalls with a height of 5 and 10 m respectively, and Kubu Jambu waterfall (12 m). In general, the orientation of the faults of Mt. Betung was northeast-southwest. The faults are also associated with several waterfalls found in the field. From the joint data processing, it can be interpreted that the fault formed on Betung Mountain is normal. The lithology of Betung Mountain is dominated by volcanic deposits in the form of tuffs. In certain rivers, there are outcrops of lava igneous rock in the form of Andesites. Andesite lava in the northern and southern parts of Betung Mountain has different characteristics.